Pemantauan Status Gizi pada Anak dengan HIV AIDS - Erindra Budi Cahyanto; Sri Mulyani; Ika Sumiyarsi Sukamto; Angesti Nugraheni; Mujahidatul Musfiroh-Universitas Sebelas Maret Surakarta (Indonesian Journal on Medical Science, 2021)
Abstract: The number of people with HIV-AIDS (Human Immunodeficiency Virus-Acquired Immunodefficiency Syndrome) continues to increase every year in line with the increase in sexual behavior outside of marriage. People with HIV / AIDS also transmit the virus to their children. One of the problems in children with HIV / AIDS is malnutrition. The research objective was to determine the development of the nutritional status of children with HIV / AIDS. The subjects were all HIV / AIDS children in Yayasan Lentera Surakarta. Time series research design, measuring the variable nutritional status at several times using the parameters of body weight for age. Data collection was carried out in July-September 2019. Bath scale measuring instrument. The number of subjects was nineteen people with the incidental sampling technique. Inclusion criteria included: people with HIV / AIDS, living in a shelter, allowed by a caregiver, aged 0-12 years, not being treated in a hospital during the study. Exclusion criteria: death, not following complete weight monitoring. During the study, no subjects withdrew or were excluded from the study. The results showed that eight children had normal nutritional status and eleven children were not normal. Different test with chi square test obtained p = 0.78. There was no difference in nutritional status between the first and second measurements. Managers need to make other efforts so that the nutritional status of children in holding centers can improve.Key words: monitoring, nutritional status, children, HIV AIDS Abstrak: Jumlah penderita HIV-AIDS (Human Immunodeficiency Virus-Aquired Immunodefficiency Syndrome) terus meningkat setiap tahunnya sejalan dengan terjadinya peningkatan perilaku seks di luar nikah. Orang dengan HIV/AIDS juga menularkan virus kepada anaknya. Salah satu masalah pada anak dengan HIV/ AIDS ini adalah status gizi kurang. Tujuan penelitian mengetahui perkembangan status gizi anak dengan HIV/AIDS. Subjek adalah seluruh anak HIV/AIDS di Yayasan Lentera Surakarta. Desain penelitian time series, mengukur variabel status gizi di beberapa waktu dengan menggunakan parameter berat badan menurut umur. Pengambilan data dilakukan pada Juli-September 2019. Alat ukur timbangan bath scale. Jumlah subjek sembilan belas orang dengan teknik incidental sampling. Kriteria inklusi meliputi : penderita HIV/AIDS, tinggal di tempat penampungan, diijinkan oleh pengasuh, usia 0-12 tahun, tidak sedang mendapat perawatan di rumah sakit selama penelitian. Kriteria eksklusi : meninggal, tidak mengikuti pemantauan berat badan secara lengkap. Selama penelitian tidak ada subjek yang mengundurkan diri maupun dikeluarkan dari penelitian. Hasil penelitian didapatkan delapan anak mempunyai status gizi normal dan sebelas anak tidak normal. Uji beda dengan uji chi square didapatkan p = 0,78. Tidak ada perbedaan status gizi antara pengukuran pertama dan ke dua. Pengelola perlu melakukan upaya lain agar status gizi anak dalam penampungan dapat meningkat.Kata kunci : Pemantauaan, status gizi, anak, HIV AIDS